I'll have what she's having [large type] - Handler, Chelsea (Random House Large Print, 2025)
"At ten years old, Chelsea opened a lemonade stand and realized she'd make more money if the drinks were spiked. So she added vodka to her recipe and used her earnings to upgrade herself to first-class on a family vacation-leaving her parents and siblings in coach. At nineteen, she moved to Los Angeles and got fired from her temp job when she admitted she didn't know how to transfer calls. She played pickleball with the scions of an American dynasty. She sexted a governor. She shared psychedelics with strangers in Spain. When she accidentally ended up at dinner with Woody Allen, she decided she wouldn't leave the table without asking him a very pointed personal question. She went on national television and talked about having threesomes. Chelsea Handler has never been one to hold back. But this life of adventure and absurdity is only part of her story. Chelsea's truest calling is showing up for her family-canine and human, biological and chosen. She's come to embrace spending time with herself, meditating, remaining open to love, and ending relationships with grace when that's what's called for. She is a sister to the many women who rely on her"--